Amanda Pig and the Really Hot Day - Van Leeuwen, Jean; Schweninger, Ann (New York : Dial Books for Young Readers, 2005)
Amanda Pig and her family and friends try to find different ways to beat the heat.
"Level 2"--P. [4] of cover.
1.8.
Keywords: Pigs -- Fiction; Heat -- Fiction; Family life -- Fiction